Microstructure and Mechanical Properties of Brass-Clad Copper Stranded Wires in High-Speed Solid/Liquid Continuous Composite Casting and Drawing - Yu Lei; Xiao Liu; Yanbin Jiang; Fan Zhao; Xinhua Liu; Jianxin Xie (Metals)
A solid/liquid continuous composite casting technology was developed to produce brass-clad copper stranded wire billets efficiently with continuous casting speeds ranging from 200 mm/min to 1000 mm/min. As the casting speed increased, the microstructure of the brass cladding transformed at an angle to the radial direction. The wire billet prepared at a casting speed of 600 mm/min was then subjected to drawing. As the percentage reduction in area of the billet increased from 11.9 to 81.5% during the drawing process, the tensile strength improved from 336 MPa to 534 MPa, while the elongation after fracture decreased from 30.1 to 4.7%. Meanwhile, dislocation, dislocation cells, and microbands successively formed in the pure copper strand wires, while twins, shear bands, dislocation pile-ups, and secondary twins gradually formed in the brass cladding. During the drawing process, the interface between copper and brass remained metallurgically bonded, exhibiting coordinated deformation behavior. This paper clarified the evolution of microstructure and mechanical properties of brass-clad copper stranded wires in high-speed solid/liquid continuous composite casting and drawing, which could provide important reference for industrial production.